Pengembangan Bahan Ajar Berbasis Android pada Materi Konsep Mol Di SMAN 4 Kota Bengkulu - Pica Lestari; Dewi Handayani; Febrian Solikhin (ALOTROP, 2023)
The era of the industrial revolution 4.0 in education is characterized by the use of technology in the learning process. This study aims to test the feasibility, test student responses and see student learning outcomes on android-based teaching materials on the mole concept material at SMAN 4 Kota Bengkulu. The research was conducted using the Research & Development (R&D) method using a 4D development model which was limited to the 3D stage (Define, Design and Development). The feasibility test of android-based teaching materials is seen through the assessment of media and material experts, test student responses on small-scale and large-scale tests and student learning outcomes from the N-Gain score. The assessment of the feasibility of android-based teaching materials was carried out by two media and materials experts respectively. The results of the feasibility obtained are the results of media validation 91% and the results of material validation 88.33% with a very feasible category. Student response tests were carried out on a small and large scale. Determination of small-scale and large-scale samples with a normality test for all students of class X SMAN 4 Kota Bengkulu TA 2020/2021, obtained 9 students of class X IPA 1 as samples of the small-scale response test and 34 students of class X IPA 2 as samples of large-scale response test. The results of the small-scale student response test are 91.79% and the large-scale response test results are 85.9%, with a very good category. Learners on a large scale are also seen from their learning outcomes from the N-Gain score obtained, which is 0.62 or is in the medium category. The results obtained show that android-based teaching materials on the mole concept material are very feasible to be used in the learning process. Keywords: Development Research, Teaching Materials, Android, Mole Concept